2019
DOI: 10.1111/apt.15138
|View full text |Cite
|
Sign up to set email alerts
|

Studies of salivary pepsin in patients with gastro‐oesophageal reflux disease

Abstract: Background: Gastro-oesophageal reflux disease (GERD) is difficult to diagnose without invasive testing. Peptest (RD Biomed, Hull, UK) is a recently marketed diagnostic tool which aims to quantify salivary pepsin as a marker of reflux, providing a rapid alternative to invasive procedures. Aim:To evaluate optimal timing for sampling, and to evaluate the accuracy of Peptest against an independent measure. Methods: Thirty diagnosed GERD patients (12 female, mean age 49 [range 20-72])and 20 asymptomatic subjects (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 25 publications
0
17
0
1
Order By: Relevance
“…A promising non-invasive test to diagnose reflux, although still controversial in its clinical applications, is the salivary detection of pepsin [43,44]. Pepsin is a proteolytic enzyme secreted in the gastric fundus as pepsinogen and activated in the acidic environment: its identification in non-gastric sites can detect the presence of significant reflux.…”
Section: Diagnosismentioning
confidence: 99%
“…A promising non-invasive test to diagnose reflux, although still controversial in its clinical applications, is the salivary detection of pepsin [43,44]. Pepsin is a proteolytic enzyme secreted in the gastric fundus as pepsinogen and activated in the acidic environment: its identification in non-gastric sites can detect the presence of significant reflux.…”
Section: Diagnosismentioning
confidence: 99%
“…1) to detect pepsin in saliva/sputum has shortened the salivary pepsin assay to several minutes and offered a strong predictive value for LRPD/GERD diagnosis [22] . There are several studies evaluating the diagnostic value of Peptest for LRPD/GERD, but they showed different results [19,22,28–41] …”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the current data are inconclusive or negative ( Ocak et al, 2015 ; Yadlapati et al, 2016 ). For example, despite the fact that salivary pepsin has been proven in some studies to aid in the diagnosis of laryngopharyngeal reflux ( Hayat et al, 2014 ; Sereg-Bahar et al, 2015 ; Spyridoulias et al, 2015 ), recent studies have failed to demonstrate the test’s clinical utility ( Yadlapati et al, 2016 ; Race et al, 2019 ). Defining the optimal saliva collection protocol, or detecting pepsin by other means such as sputum, may aid in the development of this test as a viable GERC detection tool.…”
Section: Diagnosismentioning
confidence: 99%